2000
DOI: 10.1046/j.1365-2273.2000.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Head and neck basal cell carcinoma: treatment using a 2-mm clinical excision margin

Abstract: Treatment of basal cell carcinoma (BCC) should completely remove the tumour whilst preserving the maximum amount of normal surrounding skin. Therefore, treatment is a compromise between safe excision margins and obtaining a satisfactory cosmetic result. We report the results of a prospective study of 63 patients who underwent excision of well-demarcated BCCs in the head and neck region. The surgical excision margin used was 2 mm. Histological assessment confirmed complete excision in 95% and there was no evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 18 publications
(22 reference statements)
4
41
0
6
Order By: Relevance
“…Our choice of margins was based on previous studies of 1-to 2-mm margins for small primary BCCs. 3,14 We, however, found that narrow-margin elliptical excision with margins up to 3 mm is only 80% effective in clearing these tumors. This is well below the 95% standard for tumor clearance that is expected in cutaneous surgical oncology.…”
Section: Discussionmentioning
confidence: 96%
“…Our choice of margins was based on previous studies of 1-to 2-mm margins for small primary BCCs. 3,14 We, however, found that narrow-margin elliptical excision with margins up to 3 mm is only 80% effective in clearing these tumors. This is well below the 95% standard for tumor clearance that is expected in cutaneous surgical oncology.…”
Section: Discussionmentioning
confidence: 96%
“…BBC mainly due to cumulative sun exposure over long time and many lines of treatment have been practiced including surgical excision, radiotherapy, electro-dissection, Mohs 16 technique, cryosurgery and curettage 4,12 . This study shows that, surgery is the main line of treatment practiced by surgeons for BCC and it shows the incidence of BBC in non-melanoma skin cancer is about 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Det finnes imidlertid ingen konsensus om adekvate marginer ved vanlig eksisjon -alt fra 2 mm til 15 mm er anbefalt (27,28,38,39). Det finnes mange studier der man har forsøkt å definere hva som er adekvate marginer, men i disse studiene er verken svulstene eller pasientene godt nok beskrevet for å kunne trekke sikre konklusjoner.…”
Section: Vevssparendeunclassified